Rare bird documentation form for Peregrine Falcon at Half-Moon Lake in Hawkeye Wildlife Area, unknown year - Newlon, Michael C.et al
Rare bird documentation form for a Peregrine Falcon at Half-Moon Lake in Hawkeye Wildlife Area in Johnson County, IA on September 27, unknown year. Epson - sheet feed